Taunton's complete illustrated guide to - Bird, Lonnie (Taunton Press, 2005)
This step-by-step shop reference, culled from the first six volumes of Taunton's Complete Illustrated Guides, covers all of the fundamental techniques every woodworker needs to know. Organized for quick access, this book makes it easy to find the information you are looking for. Over 1,200 photos and drawings illustrate how to accomplish essential woodworking tasks from setting up a shop to finishing